Temperature- and chemical-induced neurotoxicity in zebrafish - Toni, Mattia; Arena, Chiara; Cioni, Carla; Tedeschi, Gabriella (Frontiers in Physiology, 2023)
Throughout their lives, humans encounter a plethora of substances capable of inducing neurotoxic effects, including drugs, heavy metals and pesticides. Neurotoxicity manifests when exposure to these chemicals disrupts the normal functioning of the nervous system, and some neurotoxic agents have been linked to neurodegenerative pathologies such as Parkinson's and Alzheimer's disease. The growing concern surrounding the neurotoxic impacts of both naturally occurring and man-made toxic substances necessitates the identification of animal models for rapid testing across a wide spectrum of substances and concentrations, and the utilization of tools capable of detecting nervous system alterations spanning from the molecular level up to the behavioural one. Zebrafish (Danio rerio) is gaining prominence in the field of neuroscience due to its versatility. The possibility of analysing all developmental stages (embryo, larva and adult), applying the most common “omics” approaches (transcriptomics, proteomics, lipidomics, etc) and conducting a wide range of behavioural tests makes zebrafish an excellent model for neurotoxicity studies. This review delves into the main experimental approaches adopted and the main markers analysed in neurotoxicity studies in zebrafish, showing that neurotoxic phenomena can be triggered not only by exposure to chemical substances but also by fluctuations in temperature. The findings presented here serve as a valuable resource for the study of neurotoxicity in zebrafish and define new scenarios in ecotoxicology suggesting that alterations in temperature can synergistically compound the neurotoxic effects of chemical substances, intensifying their detrimental impact on fish populations.